2004
DOI: 10.1111/j.1095-8339.2004.00181.x
|View full text |Cite
|
Sign up to set email alerts
|

Pollination specialization and time of pollination on a tropical Venezuelan plain: variations in time and space

Abstract: Levels of specialization of the pollination systems were evaluated in 155 plant species from the Venezuelan Central Plain. In all, 29 pollination systems were found, resulting from various combinations of nine pollen-vector types or pollinating agent classes. The number of pollen-vector types composing a pollination system ranged from one to five. Ninety-one species were pollinated by only a single pollen-vector type; the frequency of pollination systems fell monotonically with increasing number of constituent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
44
0
23

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(74 citation statements)
references
References 45 publications
7
44
0
23
Order By: Relevance
“…However, polyphilous animal pollination seems to be associated with the evolution of dioecy from an ancestral hermaphrodite sexual system. The temporal frequency distribution of pollination indicated that polyphily tends to increase during the dry-rainy transition period in the forest and the community level (Ramı´rez, 2004b). Under such circumstances, polyphily is phenologically biased, and consequently, seems to act as a selective force for evolution of dioecy during the dry-rainy transition period.…”
Section: Sexual Systemsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, polyphilous animal pollination seems to be associated with the evolution of dioecy from an ancestral hermaphrodite sexual system. The temporal frequency distribution of pollination indicated that polyphily tends to increase during the dry-rainy transition period in the forest and the community level (Ramı´rez, 2004b). Under such circumstances, polyphily is phenologically biased, and consequently, seems to act as a selective force for evolution of dioecy during the dry-rainy transition period.…”
Section: Sexual Systemsmentioning
confidence: 98%
“…Information about plant pollination systems was established according to two criteria of specialization examined previously: qualitative and quantitative forms (Ramı´rez, 2004b). Plant species were categorized dealing principally with the character of visits received (lightly modified from Faegri and Van der Pijl, 1979, p. 48).…”
Section: Pollinationmentioning
confidence: 99%
“…Since bees depend exclusively on floral resources for their survival, they are the most frequent visitors found on flowers, and were reported as the most diverse and abundant group of floral visitors, as well as the main pollinators in several plant communities (Ramirez 1989, Barbosa 1997, Momose et al 1998, Oliveira & Gibbs 2000, Machado & Lopes 2004, Ramirez 2004, Freitas & Sazima 2006. Flies and wasps, after bees, were the predominant floral visitors recorded in this study, as well as in cerrado and high-altitude grasslands (Barbosa 1997, Freitas & Sazima 2006, while beetles and lepidopterans were less represented in all three communities.…”
Section: Discussionmentioning
confidence: 99%
“…Atualmente existe vasta literatura indicando que os sistemas de polinização das angiospermas se distribuem em um contínuo entre os extremos de generalização e especialização (Fenster et al 2004, Ramírez 2004, Freitas & Sazima 2006, Waser & Ollerton 2006 e uma das questões que emerge desse cenário é o entendimento dos fatores que estão ligados ao surgimento e manutenção de sistemas de polinização com alto grau de especialização (Westerkamp 1997, Aigner 2001, Fenster et al 2004, Cane & Sipes 2006. De acordo com o princípio de Stebbins (1970) do polinizador mais efetivo, uma planta deve especializarse no polinizador mais eficaz e mais abundante quando a disponibilidade deste é confiável.…”
unclassified